PNPLA3 I148M gene variant and chronic kidney disease in type 2 diabetic patients with NAFLD: Clinical and experimental findings. (15th March 2020) - Mantovani, Alessandro; Taliento, Alice; Zusi, Chiara; Baselli, Guido; Prati, Daniele; Granata, Simona; Zaza, Gianluigi; Colecchia, Antonio; Maffeis, Claudio; Byrne, Christopher D.; Valenti, Luca; Targher, Giovanni
Abstract: Background and Aims: Emerging evidence suggests an association between patatin‐like phospholipase domain‐containing protein‐3 ( PNPLA3 ) rs738409 (I148M protein variant) and risk of chronic kidney disease (CKD), but the mechanisms underpinning this association are poorly understood. Methods: We studied 157 patients with type 2 diabetes (T2DM) who underwent ultrasonography and vibration‐controlled transient elastography for diagnosing nonalcoholic fatty liver disease (NAFLD). CKD was defined as estimated glomerular filtration rate (e‐GFR) <60 mL/min/1.73 m 2 and/or abnormal albuminuria. We surveyed PNPLA3 mRNA expression in human tissues, using the liver as a positive control, and also measured PNPLA3 mRNA and protein expression levels in human cell lines represented in the kidney and the liver. Results: In all, 112 patients had NAFLD and 43 had CKD. Patients homozygous for the I148M variant (n = 11) had lower e‐GFR levels (60.6 ± 11.7 vs 77.8 ± 15.9 vs 83.5 ± 16.5 mL/min/1.73 m 2, P = .0001) and higher prevalence of CKD (63.6% vs 24.2% vs 25.0%, P = .028), compared to those with I/M (n = 66) and I/I (n = 80) PNPLA3 genotype. The association of I148M homozygosity with lower e‐GFR levels ( P < .0001) and higher risk of CKD (adjusted‐odds ratio 6.65; 95% CI 1.65‐26.8, P = .008) was independent of liver disease severity (as detected by liver stiffness ≥7kPa) and other risk factors. PNPLA3 mRNA expression was greatest in liver and renal cortex, and podocytes showed high PNPLA3 mRNA and protein levels, comparable to that of hepatocytes and hepatic stellate cells respectively. Conclusions: The PNPLA3 I148M variant was associated with CKD, independently of common renal risk factors and severity of NAFLD PNPLA3 expression levels were particularly high in renal podocytes.